2006
DOI: 10.1021/jo0601462
|View full text |Cite
|
Sign up to set email alerts
|

Peroxyl Radical Clocks

Abstract: A series of peroxyl radical clocks has been developed and calibrated based on the competition between the unimolecular beta-fragmentation (k(beta)) of a peroxyl radical and its bimolecular reaction with a hydrogen atom donor (k(H)). These clocks are based on either methyl linoleate or allylbenzene and were calibrated directly with alpha-tocopherol or methyl linoleate, which have well-established rate constants for reaction with peroxyl radicals (k(H-tocopherol) = 3.5 x 10(6) M(-1) s(-1), k(H-linoleate) = 62 M(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(125 citation statements)
references
References 21 publications
2
121
0
Order By: Relevance
“…In methyl linoleate autoxidation, the rate constant k inh for -tocopherol is 3.8 x 10 6 M -1 s -1 (Tallman et al 2001), which is ca. 60,000 times faster than the self-propagation reaction of methyl linoleate (k=62 M -1 s -1 , Roschek et al 2006). Kinetic studies suggest that the stoichiometric value for -tocopherol is two (Burton & Ingold 1981) i.e.…”
Section: Figure 12mentioning
confidence: 94%
“…In methyl linoleate autoxidation, the rate constant k inh for -tocopherol is 3.8 x 10 6 M -1 s -1 (Tallman et al 2001), which is ca. 60,000 times faster than the self-propagation reaction of methyl linoleate (k=62 M -1 s -1 , Roschek et al 2006). Kinetic studies suggest that the stoichiometric value for -tocopherol is two (Burton & Ingold 1981) i.e.…”
Section: Figure 12mentioning
confidence: 94%
“…The primary products of PL oxidation are mainly isomeric hydroperoxides [9,12,[57][58][59]. Lecithins are easily dissolved in organic solvents to yield compact reverse micelles [60,61].…”
Section: Phospholipid Oxidationmentioning
confidence: 99%
“…Lecithins are easily dissolved in organic solvents to yield compact reverse micelles [60,61]. In aqueous solutions, lecithin forms multilamellar liposomes or vesicles under the action of ultrasound dispersion [12,56,62]. Using the DLS method, it was found that, at egg lecithin concentrations 10-90 mg/mL, the size of microaggregates observed are equal to 5-6 nm in organic solvents and in water, liposomes are formed with a wide size distribution of 60-1000 nm.…”
Section: Phospholipid Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the effect of the isotope reinforcement on the propagation rate constants of Lin autoxidation as compared to that of 11,11-D 2 -Lin, we performed parallel clocking experiments utilizing a linoleate peroxyl radical clock [6,23,24], as well as competition experiments by co-oxidizing 11,11-D 2 -Lin and Lin in solution.…”
Section: Kinetic Measurements Reveal a Large Kie For The Chain Reactimentioning
confidence: 99%